2014
DOI: 10.1111/hex.12196
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' perceptions of the value of prognostic models: the benefits and risks of prognostic confidence

Abstract: Background The communication of prognosis in end-of-life (EOL) care is a challenging task that is limited by prognostic uncertainty and physicians' lack of confidence in their prognostic estimates. Clinical prediction models (CPMs) are increasingly common evidence-based tools that may mitigate these problems and facilitate the communication and use of prognostic information in EOL care; however, little is known about physicians' perceptions of the value of these tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…These tools are developed to decide whether certain treatments bring enough gain in overall or progressionfree survival to be worthwhile for patients. Research has shown that oncologists tend to overestimate life expectancy of patients [7,8], and that they could benefit from using statistical tools providing survival estimates [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These tools are developed to decide whether certain treatments bring enough gain in overall or progressionfree survival to be worthwhile for patients. Research has shown that oncologists tend to overestimate life expectancy of patients [7,8], and that they could benefit from using statistical tools providing survival estimates [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They are based on patient and tumor characteristics, and preferably compare various treatment options. Research has shown that such clinical prediction models in end-of-life care are valued by physicians, because they enhance prognostic confidence and improve communication with patients, although they can also cause emotional distress in patients and raise prognostic overconfidence despite uncertainty in palliative care [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of end-of-life patients is quintessential for an adequate integration between qualitative and intensive care treatments during the ICU stay [13,14]. Notably, palliative care should not be considered as an alternative for the intensive care in these patients; this care should instead be concomitantly made available for the patients and their family early on from the ICU admission [15].…”
Section: Discussionmentioning
confidence: 99%